The role of image in people's perception of each other - Aminova Dilnoza Orifjonovna (Genius Journals, 2023)
The article focuses on the concept of image and the characteristics of image in direct perception of people. Studies devoted to the concept of image (substantial state) and the process of its formation are described. The psychological characteristics of the image in people's perception of each other are studied.
Keywords: Image; perception; personality